MEMBANGUN KINERJA PEMASARAN MELALUI MARKETING KNOWLEDGE COMPETENCE DAN MARKETING NETWORKING - Hasyim, Hasyim (JURNAL PLANS, 2017)
This research is done based on research result differences ( research gap ) and differences of discussion focus about orientation of entrepreneurial and influence of knowledge interest and also company capability to marketing performance. Besides, there are also research problem about tightening of emulation in hand made clothes industry specially at small scale industry in Semarang city whichâs owning local market so that push brooding company to be more ahead in formulating strategy to improving its performance. Some condition and factor above were importance to be checked empirically and analyzed. Therefore the practitioner / owner in hand made clothes industry can obtain fact to support their exist in market, so the formulated strategy earn more accurate. This research is done by taking research object at small scale hand made clothes industry in Semarang, amounting to 170 company with its population element that is manager / owner. Sampling technique that used is purposive sampling. Amount of determined responder as research sample is 100 people. Analysis technique that used to interpret and analyze data in this research is technique of Structural Equation Model (SEM) of software package of AMOS. Result of examination proven hypothesis that factor entrepreneurial orientation and knowledge of market become positive effect of marketing capability and marketing performance. It is mean high significance of each other variables. As for model which is raised in this research can be accepted posed at by index according to where value of GFI 0,900, value of chi-square 87,987, probability value 0,084, value of TLI 0,965 and value of CFI 0,973, all have up to standard although value of AGFI 0,853 accepted by marginal.Â Keywords : Â Entrepreneurial Orientation, Marketing Knowledge Competence, Marketing Capability, Marketing Networking, Performance